2021
DOI: 10.7150/jca.62352
|View full text |Cite
|
Sign up to set email alerts
|

The Role of miRNAs during Endoplasmic Reticulum Stress Induced Apoptosis in Digestive Cancer

Abstract: Digestive cancer is one of the leading causes of cancer mortality in the world. Despite a number of studies being conducted, the exact mechanism for treating digestive cancer has not yet been fully understood. To survive, digestive cancer cells are subjected to various internal and external adverse factors, such as hypoxia, nutritional deficiencies or drug toxicity, resulting in accumulation of misfolded and unfolded protein in endoplasmic reticulum (ER) lumen further leading to ER stress and the unfolded prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…Wan et al, 2021 reported that miRNA-140-3p represses the proliferation of lung adenocarcinoma cells by targeting thymidylate synthetase [70]; Hu et al, 2022 also reported that miR-140-3p inhibits the progression of NSCLC by targeting Janus kinase 1 [71]. One miRNA may have multiple targets, so it plays a variety of physiological functions [72][73][74]. This makes the results of miR-140-3p targeting on other targets reported in these articles do not affect the finding that miR-140-3p can target on ADAM10 in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Wan et al, 2021 reported that miRNA-140-3p represses the proliferation of lung adenocarcinoma cells by targeting thymidylate synthetase [70]; Hu et al, 2022 also reported that miR-140-3p inhibits the progression of NSCLC by targeting Janus kinase 1 [71]. One miRNA may have multiple targets, so it plays a variety of physiological functions [72][73][74]. This makes the results of miR-140-3p targeting on other targets reported in these articles do not affect the finding that miR-140-3p can target on ADAM10 in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNAs control ER stress in digestive cancer with the involvement of FOXO ( Table 2 ) [ 1 ]. miR-132-3p is overexpressed in gastric cancers [ 130 ].…”
Section: Relationship Between Mirna Akt Effectors and Cell Functionsmentioning
confidence: 99%
“…miRNAs are responsible for post-transcriptional gene regulation and are classified according to their oncogenic and tumor suppression functions in the regulation of diverse cell functions [ 1 ]. miRNAs are known to have several functions in the regulation of proliferation, apoptosis [ 2 ], autophagy [ 3 , 4 , 5 ], endoplasmic reticulum (ER) stress [ 1 , 6 ], ferroptosis [ 7 , 8 , 9 , 10 ], necroptosis [ 11 , 12 , 13 , 14 ], DNA damage response (DDR) [ 15 , 16 , 17 ], senescence [ 18 , 19 ], and migration [ 20 , 21 , 22 , 23 ] relating to cancer cells [ 23 , 24 , 25 ]. In the following, we briefly introduce the background for these cell functions and their relationships to miRNA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers indicate that the presence of endothelial dysfunction, atherosclerosis, and hypertension in OSA may be associated with up-regulations or down-regulations of some miRNAs [ 116 , 117 , 118 , 119 ]. Recent studies found that several miRNAs could influence IH process and affect hypoxia-induced cell apoptosis [ 120 ]. Some miRNAs up-regulated or down-regulated by hypoxia are direct targets of HIF-1α, HIF-2α, NF-κB, or their responsive genes, or some inflammatory signalings [ 121 , 122 , 123 , 124 ].…”
Section: Microrna (Mirna) In Osamentioning
confidence: 99%